Electronic civil lawsuit proceedings comparative study - تارا سعيد الدباغ (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
The electronic development has imposed itself on all areas of life, including the legal field, as the technological developments have greatly affected the legislations issued by the legislator, as the legislator tries hard to keep pace with technological developments in various fields. In the field of litigation, the courts seek to make the most of modern technologies And the courts and the law behind them to resort to dealing with this type of courts only serve the parties (the citizen) and the courts also, the advantages of resorting to this type of courts are numerous, they are easy too much of the right of litigation, as the parties to the case they can raise their claim electronically, as well as these courts save time effort and reduce the expenses spent by the parties to the suit, complete confidentiality of the plaintiff and provide, as the litigation remotely provides complete secrecy. The electronic filing system has many advantages. It provides a kind of technology that allows lawyers and litigants to submit legal documents in an electronic manner according to an integrated system. This system also reduces the cost of excessive litigation fees and eliminates the huge quantities of documents and documents related to the case that are filled Which allows the courts to function more effectively. The system also provides the possibility of receiving documents at any time daily, even on holidays and public holidays, for 24 hours. Therefore, jurisprudence tried to apply the new concepts of electronic evidence to the existing rules of evidence. Faced with this situation, jurisprudence began to question the degree of legal validity that the law of evidence could give to electronic signatures, and whether the traditional rules of the law of evidence could confer the power of electronic documents to the same degree as the paper documents. The electronic development has imposed itself on all areas of life, including the legal field, as the technological developments have greatly affected the legislations issued by the legislator, as the legislator tries hard to keep pace with technological developments in various fields. In the field of litigation, the courts seek to make the most of modern technologies And the courts and the law behind them to resort to dealing with this type of courts only serve the parties (the citizen) and the courts also, the advantages of resorting to this type of courts are numerous, they are easy too much of the right of litigation, as the parties to the case they can raise their claim electronically, as well as these courts save time effort and reduce the expenses spent by the parties to the suit, complete confidentiality of the plaintiff and provide, as the litigation remotely provides complete secrecy. The electronic filing system has many advantages. It provides a kind of technology that allows lawyers and litigants to submit legal documents in an electronic manner according to an integrated system. This system also reduces the cost of excessive litigation fees and eliminates the huge quantities of documents and documents related to the case that are filled Which allows the courts to function more effectively. The system also provides the possibility of receiving documents at any time daily, even on holidays and public holidays, for 24 hours. Therefore, jurisprudence tried to apply the new concepts of electronic evidence to the existing rules of evidence. Faced with this situation, jurisprudence began to question the degree of legal validity that the law of evidence could give to electronic signatures, and whether the traditional rules of the law of evidence could confer the power of electronic documents to the same degree as the paper documents.